A Successful Medical Management of Enterococcal Endocarditis Presenting as Cellulitis. Issue 1 (June 2022) - Kataria, Riya; Senthil, N.; Lakshmanan, Suja; Anil, Archa Anna
Infective endocarditis is an infection commonly caused by bacterial pathogens and is known to affect intracardiac structures. We herein report a previously healthy man who presented with complications of infective endocarditis caused by Enterococcal faecalis and was further managed with appropriate antibiotics without the needed surgical interventions.